1987
DOI: 10.1007/bf02370641
|View full text |Cite
|
Sign up to set email alerts
|

Response of cereals to nitrogen in sole cropping and intercropping with different legumes

Abstract: The response of sole and intercropped cereal to nitrogen fertilization was compared in three contrasting cropping systems, sorghum/pigeonpea, maize/groundnut, and sorghum/cowpea. The cereal in these systems responded to nitrogen similarly as in sole cropping, although different legumes affected the cereal differently. There was no current season benefit from the legume, whether it matured earlier or later than the cereal, and for high yields the cereal in intercropping needs fertilizer application. Response to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
20
0

Year Published

1990
1990
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 12 publications
4
20
0
Order By: Relevance
“…Legumes commonly yield less dry matter when intercropped than do solecropped legumes (Danso et al, 1987;Rao et al, 1987), as was the case for the overall treatments for Leucaena in both experiments. The lack of significant difference between treatments suggests that sorghum's presence exerted little, if any, direct influence on the amount of N made available.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…Legumes commonly yield less dry matter when intercropped than do solecropped legumes (Danso et al, 1987;Rao et al, 1987), as was the case for the overall treatments for Leucaena in both experiments. The lack of significant difference between treatments suggests that sorghum's presence exerted little, if any, direct influence on the amount of N made available.…”
Section: Discussionmentioning
confidence: 82%
“…Under these conditions, the N returned to the soil is primarily through belowground processes and whatever limited litter fall is allowed. Whether a significant amount of N can accrue through these processes and whether this N is available to the companion crops remains controversial (Danso et al, 1987;Rao et al, 1987;Ta et al, 1986).…”
Section: Introductionmentioning
confidence: 99%
“…The legume typically suffers competition from the cereal which results in lower yield in intercropping compared with sole-cropping moreover addition of N fertilizer may impede the growth due to greater competition from increased cereal growth. (Searle et al, 1981;Ofori and Stern, 1986;Rao, Rego and Willey, 1987). Replacement series are intercrop patterns in which the total density is kept constant although the proportion of each species varies proper to its recommended sole-cropping and in additive series the species are grown in a way that the overall density exceeds 100% which induces the most productive intercrops (Fukai and Trenbath, 1993).…”
mentioning
confidence: 99%
“…These results were supported by the findings of Samui et al (1979), Reddy et al (1986), Abdulsalam and Subramaniam (1988), Purushotham et al (1988), Raju et al (1990), Dubey et al (1991) Panda et al (1999) and Bindra et al (2000). Many researchers also reported that cereal component in legumes based intercropping yielded more at higher levels of nitrogen application (Reddy et al 1980;Ramesh and Surve 1984;Ofori and Stern 1986;Ezumah et al 1987;Rao et al 1987;Kaushik and Gautam 1987;Chowdhury and Rosario 1992;Rafey and Prasad 1992;Bhagat and Dhar 1995;Kushwaha and Chandel 1997;Mandal et al 2000;Sarwagi and Tripathi 1999;Shivay et al 1999;Shivay and Singh 2000;Singh, 2006b). Whereas, same were failed to show its effect on pigeonpea (Table 3 and 4).…”
Section: Growth Yields and Pigeonpea Grain Equivalent Yieldmentioning
confidence: 99%